Determinants of Food Security Under Different Land Use Systems: Example of Pastoralists and Agro-Pastoralists in Northeastern Ethiopia - Habtamu Abaynew; Jema Haji; Beyan Ahmed; Vladimir Verner (Land)
The issue of ensuring food and nutrition security has become a prominent item on the global agenda, particularly for low-income countries with high population growth rates. Despite the implementation of numerous policies and programs with the objective of enhancing household calorie intake, food insecurity is worsening in Ethiopia. It is crucial to comprehend the principal factors influencing food security, as this knowledge is essential for implementing effective interventions to enhance food security. Therefore, this study aimed to estimate the food security status of households, measure the extent and severity of food insecurity, and identify the determinants of food security in Northeastern Ethiopia. The data for this study were collected through key informant interviews, focus group discussions, and a multi-stage sampling method, which involved the selection of 300 households. Descriptive and inferential statistics, the Foster–Greer–Thorbecke (FGT) index, and a probit model were employed to analyze the collected data. The results indicate that 41.67% of the sample households were food secure. By decomposing the results to the two land use systems, 34.62% and 50.69% of the pastoral and agro-pastoral households were food secure, respectively, indicating that agro-pastoral households were relatively more food secure than pastoral counterparts. Furthermore, the gap and severity of food insecurity among the sample households were calculated using FGT indices, resulting in a value of 15.02% and 5.31%, respectively. The probit model revealed that educational attainment, the number of milking cows, cultivated farm size, annual farm income, and participation in off-farm activities were significant predictors of improved household food security status. The findings of this study suggest that policies aimed at addressing food insecurity should consider livelihood diversification, the promotion of education and training, and the strengthening of institutional and technological environments.